Pro EJB 3: Java Persistence API - Keith, Mike (Apress, 2012)
The word enterprise is arguably one of the most overused terms in software development today. And yet, when someone states that they are developing an enterprise application, invariably a single word comes to mind: information. Enterprise applications are defined by their need to collect, transform and report on vast amounts of information. And, of course, that information does not simply exist in the ether. Storing and retrieving data is a multibillion dollar business, as evidenced by the burgeoning enterprise integration systems (EIS) and enterprise application integration (EAI) companies that have sprung up in recent years.